2021
DOI: 10.1371/journal.pone.0248952
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hemophilia Early Arthropathy Detection with Ultrasound (HEAD-US) score and Hemophilia Joint Health Score (HJHS) in patients with hemophilic arthropathy

Abstract: Background Hemophilic arthropathy, a condition manifested as joint destruction due to spontaneous joint bleeding, is one complication of hemophiliac patients. Early detection and intervention may improve the outcome, in which ultrasonography can be an ideal modality with the introduction of HEAD-US (Hemophilia Early Arthropathy Detection with Ultrasound) protocol. Studies have shown US benefit in hemophiliac patients, including its potential as an alternative for the Hemophiliac Joint Health Score (HJHS) syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…In addition, the majority of studies were not specifically designed to compare physical examination and ultrasound for detection of synovial proliferation specifically, resulting in potential selection and/or information bias in 9 of 15 studies. While 12 of 15 included studies reported on the correlation between HJHS and ultrasound 11,12,46,47,24,29,[39][40][41][42]44,45 and 7 of 10 aimed at investigating the correlation between HJHS and ultrasound, 11,29,39,40,44,45,47 only De la Corte-Rodriguez et al 29 aimed at comparing the separate items of the HEAD-US and HJHS.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…In addition, the majority of studies were not specifically designed to compare physical examination and ultrasound for detection of synovial proliferation specifically, resulting in potential selection and/or information bias in 9 of 15 studies. While 12 of 15 included studies reported on the correlation between HJHS and ultrasound 11,12,46,47,24,29,[39][40][41][42]44,45 and 7 of 10 aimed at investigating the correlation between HJHS and ultrasound, 11,29,39,40,44,45,47 only De la Corte-Rodriguez et al 29 aimed at comparing the separate items of the HEAD-US and HJHS.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…A post hoc analysis of data from several cohort studies using the HJHS that included 62 patients with moderate or severe haemophilia found that joint health was more likely to deteriorate over 5–10 years in patients with severe disease 62 . The HJHS correlates with the HEAD‐US, and both are complementary to each other in detecting joint damage 63 . It has been suggested that early use of HJHS and ultrasound may reveal initial joint changes that often escape clinical diagnosis, 21,24,33,64–66 although prospective studies are needed to compare the outcomes and significance of early detection versus incidental findings of abnormal joint activity in the general population.…”
Section: Relationship Between Assessments For Functional Ability and ...mentioning
confidence: 99%
“…62 The HJHS correlates with the HEAD-US, and both are complementary to each other in detecting joint damage. 63 It has been suggested that early use of HJHS and ultrasound may reveal initial joint changes that often escape clinical diagnosis, 21,24,33,[64][65][66] although prospective studies are needed to compare the outcomes and significance of early detection versus incidental findings of abnormal joint activity in the general population.…”
Section: Relationship Between Assessments For Functional Ability and ...mentioning
confidence: 99%
“…Many studies have proposed the use of US in evaluating HA [4][5][6][7][8][10][11][12][13][14][15][16][17]. However, there was some disagreement regarding US ability in detecting hemosiderin deposition in hemophilic joint.…”
Section: Introductionmentioning
confidence: 99%